Reflecting on the Reasons Pros and Cons Coercive Measures for Patients in Psychiatric and Somatic Care: The Role of Clinical Ethics Consultation. A Pilot Study - Montaguti, Elena; Schürmann, Jan; Wetterauer, Charlotte; Picozzi, Mario; Reiter-Theil, Stella (Frontiers in Psychiatry, 2019)
Background and aim: Coercive measures in patient care have come under criticism leading to implement guidelines dedicated to the reduction of coercion. This development of bringing to light Clinical Ethics Support is hoped will serve as a means of building up awareness and potentially reducing the use of coercion. This study explores the specific features of Ethics Consultation (EC while dealing with coercion. Material and method: Basel EC documentation presents insight to all persons involved with a case. The EC database of two Basel University Hospitals was developed on the grounds of systematic screening and categorization by two reviewers. 100 fully documented EC cases databased from 2013 to 2016 were screened for the discussion of coercive measures (somatic hospital and psychiatry: 50% cases, respectively). Results: Twenty-four out of 100 EC cases addressed coercion in relation to a clinically relevant question, such as compulsory treatment (70.8%), involuntary committal (50%) or restricting liberty (16.6%). Only 58.3% of EC requests mentioned coercion as an ethical issue prior to the meeting. In no case was patient decisional capacity given, capacity was impaired (43.5%), not given (33.3%) or unclear (21.7%; 1 not available). Discussion: As clinical staff appears sensitive to perceiving ethical uncertainty or conflict, but less prepared to articulate ethical concern, EC meetings serve, to “diagnose” and “solve” the ethical focus of the problem(s) presented in EC. Patient decisional incapacity proved to be an important part of reasoning, when discussing the principle of harm prevention. While professional judgment of capacity remains unsystematic, rationality or even ethicality of decision making will be hampered. The documented EC cases show a variety of decisions about whether or not coercion was actually applied. Ethical reasoning on the competing options seemed to be instrumental for an unprejudiced decision complying with the normative framework and for building a robust consensus. Conclusions: The recommendation is whether EC should be used as a standard practice whenever coercion is an issue - ideally before coercion is applied, or, otherwise. Moreover, more efforts should be made towards early and professional assessment of patient capacity and advance care counseling including the offer of advance directives.